Quality of life during the COVID-19 pandemic in Austria - Dale, Rachel; Budimir, Sanja; Probst, Thomas; Humer, Elke; Pieh, Christoph (Frontiers in Psychology, 2022)
The COVID-19 pandemic has had unprecedented effects on our daily lives. This study aimed to assess quality of life (WHOQOL-Bref physical, social, and environmental domains) at two time points during the COVID-19 pandemic with lockdown restrictions. according to gender, age and urbanization level. Representative Austrian population samples were recruited by Qualtrics® in April 2020 (t1; N=1005) and December 2020/January 2021 (t2; N=1505). ANOVAs and Bonferroni-corrected post-hoc tests were conducted to investigate differences between April 2020 and December 2020 and to compare with pre-pandemic data. Although quality of life (physical, social, and environmental domains) changed from pre-pandemic (mean scores 80, 77 & 82 respectively) to April 2020 (mean scores 72, 65, 75, all p-values <0.001), there were no significant changes between April and December (mean scores 75, 65, 75). Living location (urban vs. rural), gender, and age showed an effect on quality of life. All domains of quality of life have decreased since the onset of the pandemic and this decline has been maintained over the course of the first year of the pandemic. Creative measures should be implemented to assist people in improving one or more areas of quality of life, within the lockdown restrictions, in order to improve the overall well-being of the population.